2009
DOI: 10.1007/s00125-009-1598-y
|View full text |Cite
|
Sign up to set email alerts
|

Dysglycaemia and 90 day and 1 year risks of death or readmission in patients hospitalised for community-acquired pneumonia

Abstract: Aims/hypothesis The aim of this study was to investigate whether dysglycaemia at admission is associated with adverse events at 90 days or 1 year in a population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
11
1
1
Order By: Relevance
“…[1][2][3][4] Most previous research in this area has focused on the relationship between dysglycaemia and specific conditions 2-4 on admission to specialist care facilities (eg different intensive care units). 5 In this study, we investigate the relationship between dysglycaemia and length of hospital stay, shortterm (28-day) mortality and readmissions in an unselected acute medical unit (AMU) population.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Most previous research in this area has focused on the relationship between dysglycaemia and specific conditions 2-4 on admission to specialist care facilities (eg different intensive care units). 5 In this study, we investigate the relationship between dysglycaemia and length of hospital stay, shortterm (28-day) mortality and readmissions in an unselected acute medical unit (AMU) population.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was associated with prolonged LOS and LOIVAB, but only LOS remained significant after adjusting for confounders. Hyperglycaemia has been associated with excess mortality in patients admitted to ICUs [17] and in CAP patients with hyperglycaemia [9, 10, 18], although the literature is inconsistent [13, 14]. In 2012, L epper et al [10] found, in a large prospective multicentre cohort study of CAP, that hyperglycaemia is strongly associated with 90 day mortality in patients without DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that hyperglycaemia may be associated with severe outcome in a range of conditions, including sepsis [1, 7, 8]. In some CAP studies, an association with higher mortality has also been reported [912], while others have shown no association [13, 14]. Most studies have focused on the association between hyperglycaemia and long-term mortality (28–90 day mortality) after an episode of CAP [10, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sowohl Hypo-als auch Hyperglykämien sind während stationärer Aufenthalte mit längerer Aufenthaltsdauer, schlechtem Outcome bis hin zum Tod in Verbindung zu bringen [1][2][3]. Daher zielen die meisten Leitlinien auf eine sichere Blutzuckereinstellung unter Vermeidung von Hypo-und Hyperglykämien ab.…”
unclassified